Vitrectomy and high-frequency welding-assisted endoresection оf retinal vasoproliferative tumors: a case series - M.M. Umanets; I.P. Dovgan; M. I. Marushchak; I.Y. Krynytska (Ukrainian Society of Ophthalmologists, 2024)
Background: The relative rarity of retinal vasoptoliferative tumors has resulted in a lack of ecidence-based consensus agreement on how best to treat these lesions. Therefore, there is a need for advanced techniques capable of more effective treatment of these tumors and allowing for the preservation of visual function. Purpose: To review the results of treatment of large retinal VPTs by pars plana vitrectomy with tumor endoresection and the use of high-frequency electric welding (HFEW) for achieving hemostasis. Material and Methods: We reivewed the results of surgical treatment of large retinal VPTs complicated by exudative retinal detachment, macular edema, and/or epiretinal fibrosis in 5 patients (6 eyes). Patients underwent a comprehensive eye examination (visual acuity, biomicroscopy, ophthalmoscopy, tonometry, perimetry) and imaging (ultrasound examination, and optical coherence tomography. Outcome measures included anatomical success (retinal re-attachment), visual acuity, the presence of intraoperative and postoperative hemorrhagic complications, resorption of subretinal exudates, restoration of retinal profile, and the absence of tumor recurrence over the 6-month follow-up period. Results: Total tumor removal was achieved in all cases. In addition, there was no intraoperative hemorrhage. At the 6-month follow-up examination, the best-corrected visual acuity (BCVA) ranged from 0.17 to 0.3. Over the 6-month follow-up period, the retina remained re-attached, BCVA improved, and partial resorption of hard exudates as well as restoration of the retinal profile was observed in all cases (6 eyes). Moreover, no tumor recurrence was noted. Conclusion: Vitrectomy with retinal VPT endoresection results in positive anatomical and functional outcomes, making it a method of choice in the treatment of large complicated retinal VPT resistant to more eye-sparing modalities; the HFEW technique proved to be an apt choice for intraoperative hemostasis.